Whether Environmental Performance Can Strengthen Corporate Governance Relationship To Carbon Emission Disclsoure - Ulfa Ulfa; Khomsiyah Khomsiyah (Al-Makki Publisher, 2023)
This research aims to examine the impact of the correlation between corporate governance and moderated carbon emission disclosure and environmental performance. This study used secondary data using purposive sampling techniques. Twelve companies met the specified criteria and obtained 60 data during the research period from 2017 to 2021. The data analysis technique used is